(untitled) (Journal of Orofacial Research, 2019)
Dengue is an important tropical infection. Although there are a few clinical manifestations mentioned in the literature, oral manifestations are less. Practitioner should consider dengue as possible diagnosis during oral examinations as oral manifestations may be the initial presentations in dengue infections prior to clinical presentations. In this short article, the authors summarize and discuss on orofacial manifestation in dengue.